Multiperiodic magnetic structures in Hubbard superlattices - Malvezzi, André Luiz [UNESP]; Paiva, Thereza [UNESP]; Dos Santos, Raimundo R. [UNESP] (American Physical Society (APS), 2002)
We consider fermions in one-dimensional superlattices (SL's), modeled by site-dependent Hubbard-U couplings arranged in a repeated pattern of repulsive (i.e., U>0) and free (U=0) sites. Density matrix renormalization group diagonalization of finite systems is used to calculate the local moment and the magnetic structure factor in the ground state. We have found four regimes for magnetic behavior: uniform local moments forming a spin-density wave (SDW), floppy local moments with short-ranged correlations, local moments on repulsive sites forming long-period SDW's superimposed with short-ranged correlations, and local moments on repulsive sites solely with long-period SDW's; the boundaries between these regimes depend on the range of electronic densities ρ and on the SL aspect ratio. Above a critical electronic density, ρ↑↓, the SDW period oscillates both with ρ and with the spacer thickness. The former oscillation allows one to reproduce all SDW wave vectors within a small range of electronic densities, unlike the homogeneous system. The latter oscillation is related to the exchange oscillation observed in magnetic multilayers. A crossover between regimes of thin to thick layers has also been observed.
Keywords: electron; elementary particle; fermion; magnetic field; mathematical analysis; mathematical parameters; model; oscillation